Theoretical analysis of correlations between two quantum fields exciting a three-level system using the cluster-expansion approach - Rose, Hendrik; Tikhonova, Olga V.; Meier, Torsten; Sharapova, Polina (Ultrafast Phenomena and Nanophotonics XXVI)

Coherent contributions to population dynamics in a semiconductor microcavity - Paul, J.; Rose, Hendrik; Swagel, E.; Meier, Torsten; Wahlstrand, J. K.; Bristow, A. D. (Physical Review B)

Super-Bloch oscillations with parametric modulation of a parabolic trap - Meier, Torsten; Ali, Usman (Condensed Matter)

Nonlinear down-conversion in a single quantum dot - Jonas, B.; Heinze, Dirk Florian; Schöll, E.; Kallert, P.; Langer, T.; Krehs, S.; Widhalm, A.; Jöns, Klaus; Reuter, Dirk; Schumacher, Stefan; Zrenner, Artur (Nature Communications)
Abstract Tailored nanoscale quantum light sources, matching the specific needs of use cases, are crucial building blocks for photonic quantum technologies. Several different approaches to realize solid-state quantum emitters with high performance have been pursued and different concepts for energy tuning have been established. However, the properties of the emitted photons are always defined by the individual quantum emitter and can therefore not be controlled with full flexibility. Here we introduce an all-optical nonlinear method to tailor and control the single photon emission. We demonstrate a laser-controlled down-conversion process from an excited state of a semiconductor quantum three-level system. Based on this concept, we realize energy tuning and polarization control of the single photon emission with a control-laser field. Our results mark an important step towards tailored single photon emission from a photonic quantum system based on quantum optical principles.
Keywords: General Physics and Astronomy; General Biochemistry; Genetics and Molecular Biology; General Chemistry; Multidisciplinary

Pulse shaping for on-demand emission of single Raman photons from a quantum-dot biexciton - Praschan, Tom; Heinze, Dirk; Breddermann, Dominik; Zrenner, Artur; Walther, Andrea; Schumacher, Stefan (Physical Review B)

Nonlinear down-conversion in a single quantum dot - Jonas, Björn; Heinze, Dirk Florian; Schöll, Eva; Kallert, Patricia; Langer, Timo; Krehs, Sebastian; Widhalm, Alex; Jöns, Klaus; Reuter, Dirk; Zrenner, Artur

Bound polaron formation in lithium niobate from ab initio molecular dynamics - Krenz, Marvin; Gerstmann, Uwe; Schmidt, Wolf Gero (Applied Physics A)
Abstract Polarons influence decisively the performance of lithium niobate for optical applications. In this work, the formation of (defect) bound polarons in lithium niobate is studied by ab initio molecular dynamics. The calculations show a broad scatter of polaron formation times. Rising temperature increases the share of trajectories with long formation times, which leads to an overall increase of the average formation time with temperature. However, even at elevated temperatures, the average formation time does not exceed the value of 100 femtoseconds, i.e., a value close to the time measured for free, i.e., self-trapped polarons. Analyzing individual trajectories, it is found that the time required for the structural relaxation of the polarons depends sensitively on the excitation of the lithium niobate high-frequency phonon modes and their phase relation.
Keywords: General Materials Science; General Chemistry

Two-Mode Photon-Number Correlations Created by Measurement-Induced Nonlinearity - Meier, Torsten; Hoepker, Jan Philipp; Protte, Maximilian; Eigner, Christof; Silberhorn, Christine; Sharapova, Polina R.; Sperling, Jan; Bartley, Tim (Conference on Lasers and Electro-Optics: Applications and Technology)
We demonstrate theoretically and experimentally complex correlations in the photon numbers of two-mode quantum states using measurement-induced nonlinearity. For this, we combine the interference of coherent states and single photons with photon sub-traction.

DC Ionic Conductivity in KTP and Its Isomorphs: Properties, Methods for Suppression, and Its Connection to Gray Tracking - Padberg, Laura; Quiring, Viktor; Bocchini, Adriana; Santandrea, Matteo; Gerstmann, Uwe; Schmidt, Wolf Gero; Silberhorn, Christine; Eigner, Christof (Crystals)
We study the DC conductivity in potassium titanyl phosphate (KTiOPO4, KTP) and its isomorphs KTiOAsO4 (KTA) and Rb1%K99%TiOPO4 (RKTP) and introduce a method by which to reduce the overall ionic conductivity in KTP by a potassium nitrate treatment. Furthermore, we create so-called gray tracking in KTP and investigate the ionic conductivity in theses areas. A local unintended reduction of the ionic conductivity is observed in the gray-tracked regions, which also induce additional optical absorption in the material. We show that a thermal treatment in an oxygen-rich atmosphere removes the gray tracking and brings the ionic conductivity as well as the optical transmission back to the original level. These studies can help to choose the best material and treatment for specific applications.

LLC Resonant Converter Modulations for Reduced Junction Temperatures in Half-Bridge Mode and Transformer Flux in the On-the-Fly Morphing Thereto - Rehlaender, Philipp; Wallscheid, Oliver; Schafmeister, Frank; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Assessment of mechanical and optical properties of Al 6060 alloy particles by removal of contaminants - Vieth, Pascal; Borgert, Thomas; Homberg, Werner; Grundmeier, Guido (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Analyse des Versagensverhaltens geklebter Stahl- Verbindungen beim werkstoffschonenden Entfügen in der Karosserieinstandsetzung - Chudalla, Nick; Meschut, Gerson; Teutenberg, Dominik; Wibbeke, Michael; Bartley, Aurélie

Information Model for Hybrid Prototyping in Design Reviews of Assembly Stations - Gräßler, Iris; Roesmann, Daniel; Hillebrand, Stefan; Pottebaum, Jens (Procedia CIRP ICME)
Keywords: General Medicine

Entwicklung einer Methode zur Bewertung einer stahlintensiven Mischbau-Klebverbindung eines Batteriegehäuses gegenüber mechanischer und medialer Belastung unter Berücksichtigung der Interphasenstruktur - Schmolke, Tobias; Meschut, Gerson; Vieth, Pascal; Meinderink, Dennis; Grundmeier, Guido

Experimentelle und numerische Untersuchung der Dämpfungseigenschaften geklebter Strukturen unter dynamischer Beanspruchung - Göddecke, Johannes; Meschut, Gerson; Kötz, Fabian; Matzenmiller, Anton; Damm, Jannis; Albiez, Matthias; Ummenhofer, Thomas

A Thermal Model for Recuperative Heat Engines Operating with Dense Working Fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Inguva, Venkatesh; Kenig, Eugeny Y. (Chemical Engineering Transactions)

CFD-Based Investigation of the Packing Microstructure Influence on Droplet Behavior and Film Flow - Dechert, Christopher; Kenig, Eugeny (Proceedings of the 12th international conference Distillation & Absorption 2022)

On Heat Regeneration Limitations in Heat Engines With Dense Working Fluids - Mügge, Nils; Kronberg, Alexander; Glushenkov, Maxim; Kenig, Eugeny (Heat Powered Cycles Conference 2022)

Review on mechanical joining by plastic deformation - Meschut, Gerson; Merklein, M.; Brosius, A.; Drummer, D.; Fratini, L.; Füssel, U.; Gude, M.; Homberg, Werner; Martins, P.A.F.; Bobbert, Mathias; Lechner, M.; Kupfer, R.; et al. (Journal of Advanced Joining Processes)
Mechanical joining technologies are increasingly used in multi-material lightweight constructions and offer opportunities to create versatile joining processes due to their low heat input, robustness to metallurgical incompatibilities and various process variants. They can be categorised into technologies which require an auxiliary joining element, or do not require an auxiliary joining element. A typical example for a mechanical joining process with auxiliary joining element is self-piercing riveting. A wide range of processes exist which are not requiring an auxiliary joining element. This allows both point-shaped (e.g., by clinching) and line-shaped (e.g., friction stir welding) joints to be produced. In order to achieve versatile processes, challenges exist in particular in the creation of intervention possibilities in the process and the understanding and handling of materials that are difficult to join, such as fiber reinforced plastics (FRP) or high-strength metals. In addition, predictive capability is required, which in particular requires accurate process simulation. Finally, the processes must be measured non-destructively in order to generate control variables in the process or to investigate the cause-effect relationship. This paper covers the state of the art in scientific research concerning mechanical joining and discusses future challenges on the way to versatile mechanical joining processes.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Evaluation eines digitalen Fachspezifischen Chinesischsprachkurses für Studierende des Ingenieurwesens - Hambach, Dennis (die hochschullehre. Interdisziplinäre Zeitschrift für Hochschule und Lehre)
Ziel dieser Studie ist es den digitalen moodlegestützten asynchronen Sprachkurs Fachspezifisches Chinesisch für das „Maschinenbau in China Programm“ (mb-cn) der Fakultät für Maschinenbau der Universität Paderborn zu evaluieren, um Handlungsempfehlungen für zukünftig ähnlich aufgebaute Projekte zu entwickeln. Dazu wurden im Sommersemester 2021 sechs leitfadengestützte Interviews geführt. Die Interviews wurden anschließend mithilfe von deduktiv ermittelten Kategorien, die sich aus dem Technology Acceptance Model 2 (TAM2) nach Venkatesh und Davis (2000) ergaben, nach Mayring (2015) analysiert, um abschließend die Forschungsfrage zu beantworten: „Wie bewerten mb-cn Ingenieurstudierende die wahrgenommene Nützlichkeit der digitalen Sprachlernangebote des Kurses Fachspezifisches Chinesisch?“.
Keywords: Technology Acceptance Model; Fachspezifische Chinesischsprachkurse; digitale Lehre; Moodle; Evaluation